Minimum torque ripple algorithm with fuzzy logic controller for DTC of PMSM - Adam, Ali Ahmed; Gulez, Kayhan; Erdogan, Nuh (SPRINGER-VERLAG BERLIN, 2007)
In this paper a fuzzy logic controller to minimize the torque ripples associated wit DTC (FL-DTC) of PMSM is presented. In this system, in order to attain the merits of fast torque response, the torque error, the flux error and stator flux position sector are used to select one active vector while the active switching time of this vector is selected as a result of the torque error magnitude and flux error magnitude fuzzification. The output of such fuzzy logic controller is used to adapt the inverter switching to follow the errors magnitude level. Arranging the inverter switching in this manner, results in fast torque response and minimum torque ripples as compared to the traditional HDTC. Additionally it results in less switching losses associated with SVMDTC. The simulated results show considerable torque ripple as well as current ripple reduction. The simulated results are supported with experimental results.
Keywords: interior permanent magnet synchronous motor; direct torque control; fuzzy logic; torque ripple; SYNCHRONOUS MOTOR; DRIVE; Computer Science